Stratigraphical distribution of the Ordovician conodont Erraticodon Dzik in Argentina - Heredia, Susana Emma; Carlorosi, Josefina María Teresa; Mestre García, Ana Isabel; Soria Pures, Tatiana Belén (Journal of South American Earth Sciences)
Three different species of the Ordovician genus Erraticodon Dzik are described and illustrated. E. patu Cooper is reported from the Lower-Midde Ordovician strata of the Acoite and Alto del Cóndor formations. E. cf. E. balticus and E. hexianensis from Middle Ordovician carbonate deposits of the San Juan Formation are analyzed and compared to specimens of these species from Australia, China, Newfoundland, and Baltica. E. patu and E. hexianensis are recorded for first time in the San Juan Formation of Precordillera. The elements of E. cf. E. balticus resemble closely E. balticus Dzik but lack the important denticle on the posterior process of the S elements. An evaluation of the stratigraphic occurrences of these species relative to those of key Lower and Middle Ordovician conodont species such as Trapezognathus diprion Lindström, O. intermedius Serpagli, Baltoniodus triangularis (Lindström), B. navis Lindström, Yangtzeplacognathus crassus (Chen and Zhang) and Eoplacognathus pseudoplanus (Viira) indicates they value for biostratigraphic correlation. Fil: Heredia, Susana Emma. Universidad Nacional de San Juan. Facultad de Ingeniería. Instituto de Investigaciones Mineras; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - San Juan. Centro de Investigaciones de la Geosfera y Biosfera. Universidad Nacional de San Juan. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones de la Geosfera y Biosfera; Argentina Fil: Carlorosi, Josefina María Teresa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Instituto Superior de Correlación Geológica. Universidad Nacional de Tucumán. Facultad de Ciencias Naturales e Instituto Miguel Lillo. Departamento de Geología. Cátedra Geología Estructural. Instituto Superior de Correlación Geológica; Argentina Fil: Mestre García, Ana Isabel. Universidad Nacional de San Juan. Facultad de Ingeniería. Instituto de Investigaciones Mineras; Argentina. ...